Oracles in Pandemic: Forecasts of Colombian Economic Growth in 2020 (2021)
Forecasting has allowed the economic discipline to gain power and social relevance, although it has also exposed it to public discredit. In the uncertainty that has shaped COVID-19, the determinants of Colombian annual economic growth forecasts for the year 2020 were studied and it was found that the variability of the forecasts, which range from +0,7 to -13,8%, does not depend on the evolution of the epidemiological situation, nor the institutional characteristics of those forecasting. The variability is mainly explained by the average of the most recent previous forecasts and by the central bank intervention rate.